PENGEMBANGAN MEDIA POP UP BOOK UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PELAJARAN IPAS KELAS IV MIN 1 LOMBOK TENGAH - Afriani, Andri; Lisnawati, Lisnawati (LP2M STAI Darul Kamal NW Kembang Kerang, 2025)
The aim of this research is to find out how to develop Pop up Book media on metamorphosis material (living animals) and students responses to the media in this learning. The design of this research is Research and Development (R&D) research using the ADDIE model. This study uses 2 approaches, namely quantitative and qualitative. The data collection instruments used were validation sheets and questionnairs. Data collection techniques used validation and distribution of questionnairs. Validation data and student responses were analyzed using a percentage formula. Pop Up Book media went trough several stages of expert validation with the final results of the media feasibility obtaining an average chord of 91,9% with a very feasible category. The result of students responses to the use of Pop up Book media was 0% they didn’t respond independently, 1,56% students responded as less interested, 16,80% responded as interested, and 81,64% responded as very interested. Thus it can be concluded that the Pop up Book media can increase students interest in learning